Pollution modelling and multiple-output production - Finn R. Førsund (University of Oslo, Department of Economics, 2016)
The materials balance principle points to the crucial role of material inputs in generating residuals in production processes. Pollution modelling must be of a multi-output nature. The most flexible transformation function in outputs and inputs used in textbooks is too general to make sense in pollution modelling. Specifying bads as if they are inputs, although defendable on a macro Level, hides explicit considerations of various modification activities. A complete taxonomy of inputs as to the impact on both residuals and marketed Products as joint outputs, is derived, based on factorially determined multi-output Production, thus providing information for choice of policy instruments.
Keywords: 330; multiple-outpt production; factorially determined multi output production; pollution; bads; purification; modification